Associations between Internet addiction, life satisfaction, and post-traumatic stress symptoms among disaster-exposed children and early adolescents: a three-wave longitudinal study - Shi, Wei; Yuan, Guangzhe; Chen, Zhangming; Tan, Youguo; Jiang, Lihua; Zhao, Li (Frontiers in Psychiatry, 2025)
ObjectivesPrevious studies have established links between Internet addiction, life satisfaction, and post-traumatic stress symptoms (PTSS) in individuals exposed to disasters; however, the nature of longitudinal links remains uncertain. This study aimed to determine the potential associations among Internet addiction, life satisfaction and PTSS among disaster-exposed Chinese children and early adolescents.MethodsA three-wave longitudinal design was employed over two years and included 2354 Chinese children and early adolescents aged 6 years to 14 years who directly experienced an earthquake and COVID-19. A complete longitudinal mediation method was applied to analyze data collected in three waves from 2020 to 2022 with a one-year interlude.ResultsLife satisfaction at Time 2 (T2) fully mediated the associations between Internet addiction at Time 1 (T1) and PTSS at Time 3 (T3). Internet addiction at T2 was a significant mediator of links between life satisfaction at T1 and PTSS at T3.ConclusionsThese findings underscore the pivotal role of life satisfaction in mediating the impact of early Internet addiction on long-term psychological outcomes, highlighting it as a key target for interventions aimed at enhancing mental well-being after disaster exposure. Moreover, Internet addiction mediated the link between earlier life satisfaction and later PTSS, highlighting the importance of reducing problematic Internet use to prevent long-term stress symptoms.